2018
DOI: 10.1021/acssuschemeng.7b04481
|View full text |Cite
|
Sign up to set email alerts
|

Silver Nanoparticle-Decorated Boron Nitride with Tunable Electronic Properties for Enhancement of Adsorption Performance

Abstract: In this paper, a series of silver nanoparticle (AgNP)-decorated boron nitride (Ag-BN) with different Ag amounts were successfully synthesized by a one-pot pyrolysis method and used as novel high-efficiency adsorbents for the removal of organic pollutant tetracycline (TC) and rhodamine B (RhB). According to the adsorption capacity of the samples, the obtained optimal Ag/B molar ratio was 1%. The adsorption data fitted well with the pseudo-second-order kinetics and Langmuir isotherm models with the maximum adsor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(26 citation statements)
references
References 73 publications
(110 reference statements)
2
24
0
Order By: Relevance
“…The textural properties of pristine BN and BN-P123 adsorbent were obtained by nitrogen adsorption/desorption isotherm at 77 K and the results are summarized in Table 1. As indicated in Figure 4a, the resulting isotherms display a typical type II curve based on IUPAC classification and type H3 hystersis loop in the partial pressure range 0.4-1.0, which indicates the presence of mesopores and slit shape pores [33]. There is a trivial rise in N2 adsorption-desorption isotherm of BN-P123 at lower pressure (P/P0 < 0.25), which is caused by presence of micropores [34].…”
Section: Textural Analysismentioning
confidence: 86%
“…The textural properties of pristine BN and BN-P123 adsorbent were obtained by nitrogen adsorption/desorption isotherm at 77 K and the results are summarized in Table 1. As indicated in Figure 4a, the resulting isotherms display a typical type II curve based on IUPAC classification and type H3 hystersis loop in the partial pressure range 0.4-1.0, which indicates the presence of mesopores and slit shape pores [33]. There is a trivial rise in N2 adsorption-desorption isotherm of BN-P123 at lower pressure (P/P0 < 0.25), which is caused by presence of micropores [34].…”
Section: Textural Analysismentioning
confidence: 86%
“…These materials are thermal, oxidation, and chemical resistant and can be recycled by burning, washing, and even heating in air [171]. It has been reported that the adsorption efficiency of the BN nanosheets is associated with their electronic properties and enhancement of this feature through nanohybridization with highly conductive metal nanoparticles such as Ag can bring about a superior adsorption capacity [172]. Accordingly, in a recent study [172], the BN nanosheets were surface decorated with Ag nanoparticles via a simple, one-pot pyrolysis method.…”
Section: D Inorganic Nano-adsorbentsmentioning
confidence: 99%
“…It has been reported that the adsorption efficiency of the BN nanosheets is associated with their electronic properties and enhancement of this feature through nanohybridization with highly conductive metal nanoparticles such as Ag can bring about a superior adsorption capacity [172]. Accordingly, in a recent study [172], the BN nanosheets were surface decorated with Ag nanoparticles via a simple, one-pot pyrolysis method. Such nanostructures were employed as dye adsorbents for removal of RhB (880 mg•g −1 ).…”
Section: D Inorganic Nano-adsorbentsmentioning
confidence: 99%
“…Surface modification can not only improve interfacial properties but also provide additional adsorption sites. Recently, our group demonstrates that silver nanoparticle is successfully decorated on BN through a onepot pyrolysis method [50] . The modified silver nanoparticle can tailor the electronic structure of BN nanosheets, enabling the Ag/BN materials with improved adsorption performance towards tetracycline (TC) and rhodamine B (RhB), compared with pristine BN.…”
Section: Surface Modificationmentioning
confidence: 99%